STUDI PEMANFAATAN KAWASAN LAUT PASIR DI TAMAN NASIONAL BROMO TENGGER SEMERU - Ika Kasuarina Samiasih; Tutut Sunarminto; Harnios Arief (Department of Forest Resources Conservation and Ecotourism - IPB University, 2015)
Bromo Tengger Semeru national park is the only conservation area which has a unique form laut pasir. The method used to perceptions of visitors and public use in the form of close-ended questionnaire and use Likert scale technique. Data were analyzed using descriptive and chi-square statistical test. Perceptions of respondents earn a score of 5 (somewhat agree) to the type of activities performed and the condition of the area. Respondents gave a score of 3 (disagree) to natural resources exploited. Chi square test for aspects of perception indicates that the value of X2count < X2 tabel at 0,95 < 12,59 it is stated that the answers of the respondents do not have a difference / relationship to a given question. Respondents gave a score of 5 (somewhat agree) to the impact of the economic and ecological impacts arising from use activities. Chi square test for aspects of the impact showed that value of X2count > X2 tabel at 13,83 > 7,81 it is stated that the answers of the respondents have a difference / relationship to a given question. Keywords: impact of the utilization, laut pasir, utilization of area Park.